Eksistensi Tasawuf dan Perubahan Sosial: Kajian Tokoh Syekh Burhanuddin - Latif Aswen; Yulita Yulita; Tifa Maylasandi; Dimas Kurniawan; Zainal Zainal (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Social Sufism is a practice that places significance not only on the individual, but also on the well-being of society. It is a movement that seeks to influence change in social life, deviating from the scientific traditions of Islamic boarding schools and other Islamic universities. The focus is on finding ways to change Sufism in relation to social life, especially in Indonesia. Today's modern times do not require abstinence from political power, but on the contrary, require integration and participation. Because avoidance of power implies vulnerability and ineffectiveness. Basically, social Sufism is not an exclusive and solitary practice, but rather a practice that is actively involved in the sustainable development of national society, which is the social demand and responsibility of Sufism. This is not a call for uzlah from the masses, but for active and dynamic engagement. On the other hand, Sufism must have a role and be active in life in total, whether in the social, political, economic or other fields. Therefore, the role of the Sufi must be more empirical, pragmatic and functional in addressing and viewing life in a real way.